SELF-EFFICACY AND SELF-REGULATED LEARNING FOR ENGLISH CONTENT COURSES IN ONLINE LEARNING - Sharizan; Indah Tri Purwanti; Eliwarti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This paper discusses a study that is focused on English Department students’ self-efficacy and self-regulated learning for English content courses in online learning. This study is a quantitative descriptive study that involved 114 English Department students taking in Semantic Class at Universitas Riau. The participants are selected through a saturated sampling technique, where all populations who respond to the questionnaire are the samples of this research. The data are collected from a set of questionnaires that are broadcasted online through the WhatsApp Group feature and analyzed by using descriptive statistics through SPSS Application. The findings show that the English Department students’ self-efficacy and self-regulated learning are high with a total average of 3.83 and 3.57 while learning English content courses in online learning. It can be inferred that the students who have background knowledge in operating technology and are familiar with it, are less likely to experience any problems while learning. Moreover, the understanding about self-efficacy and self-regulated learning should be more cultivating both the teachers and the students.